Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2215/cjn.03400410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cystatin C and Creatinine-based Glomerular Filtration Rate Formulas with 51Cr-EDTA Clearance in Patients with Cirrhosis

Abstract: SummaryBackground and objectives Renal function is an important predictor of survival in cirrhosis and liver transplantation. GFR estimates using serum cystatin C (CysC) are proposed as better predictors of renal function than ones on the basis of serum creatinine (Cr). Our aims were: (1) evaluate correlations between serum CysC and different methods of creatinine measurements; (2) compare CysC and Cr GFR formulas with 51 Cr-EDTA; and (3) evaluate liver-related parameters potentially influencing GFR.Design, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 37 publications
7
44
1
1
Order By: Relevance
“…GFR estimations were significantly different to inulin clearance. In the second study serum cystatin C formulas not only significantly overestimated renal clearance compared with 51 Cr-EDTA but did not provide any advantage over serum creatinine formulas [35] , and serum cystatin C values were significantly affected by the presence of ascites. Although a third study reported cystatin C to more accurately represent renal function than serum creatinine [50] .…”
Section: Alternatives To Creatinnementioning
confidence: 81%
See 2 more Smart Citations
“…GFR estimations were significantly different to inulin clearance. In the second study serum cystatin C formulas not only significantly overestimated renal clearance compared with 51 Cr-EDTA but did not provide any advantage over serum creatinine formulas [35] , and serum cystatin C values were significantly affected by the presence of ascites. Although a third study reported cystatin C to more accurately represent renal function than serum creatinine [50] .…”
Section: Alternatives To Creatinnementioning
confidence: 81%
“…It has been recommended that creatinine results used for calculating eGFR should be traceable to an IDMS reference method [34] , but the IDMS standards do not correct for the effects of chromogens. To overcome the problem that these formulae were derived from cohorts without liver disease new formulae for patients with cirrhosis have been proposed including adding the Child Turcot Pugh (CTP) score and ascites into the formula [35] . These newer formulae have been reported to show better agreement with "true" GFR, compared to the MDRD formulae, but require further external validation before they can be introduced into clinical practice.…”
Section: What Are the Alternatives To Measuring Serum Creatinine?mentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin C production is also affected by chronic liver disease, and it increases as patients progress from ChildTurcotte-Pugh stage A to C. Thus, as with serum creatinine, cystatin C also tends to overestimate kidney function, and it has not been proven to offer any advantages in assessing GFR over use of serum creatinine levels (18). Isotopic and radiocontrast methods can be used to assess kidney function in patients with cirrhosis, but they are susceptible to errors caused by redistribution within ascitic and extracellular fluid (19).…”
Section: Assessment Of Kidney Function In Patients With Cirrhosismentioning
confidence: 99%
“…17 The sum of information available to date on cystatin C-based assessment equations in patients with liver disease provides reasonable evidence in support of its use as a marker of GFR, but additional studies are needed to support regular use in clinical practice. [18][19][20][21][22][23] The characteristics of vancomycin (V) also make it a reasonable candidate to consider as a marker of kidney function. V is a tricyclic glycopeptide antibiotic commonly used in hospitalized patients with liver disease and often requires measurement of serum concentrations to evaluate therapy.…”
Section: Introductionmentioning
confidence: 99%